Effect of Age and Refractive Error on Local and Global Visual Perception in Chinese Children and Adolescents - Gan, Jiahe; Wang, Ningli; Li, Shiming; Wang, Bo; Kang, Mengtian; Wei, Shifei; Guo, Jiyuan; Liu, Luoru; Li, He (Frontiers in Human Neuroscience, 2022)
Purpose This study investigated the impact of age and myopia on visual form perception among Chinese school-age children. Methods This cross-sectional study included 1074 students with a mean age of 12.1 ± 4.7 (range = 7.3-18.9) years. The mean spherical equivalence refraction (SER) of the participants was -1.45 ± 2.07 D. All participants underwent distance visual acuity (VA), refraction measurement and local and global visual form perception test including orientation, parallelism, collinearity, holes and color discrimination tasks. Results The reaction times of emmetropes were slower than those of myopic and high myopic groups on both local (orientation, parallelism, and collinearity) and global discrimination tasks (all p < 0.05). A reduction in reaction times was found with increasing age on both local and global discrimination tasks (all p < 0.05). Age was significantly associated with both local and global visual perception performance after adjusting for gender, visual acuity and SER (orientation, β =-0.54, p < 0.001; parallelism, β = -0.365, p < 0.001; collinearity, β = -0.28, p < 0.001; holes, β = -0.319, p < 0.001; color, β =-0.346, p < 0.001). Conclusions This study revealed that both local and global visual perception improve with age among Chinese children and that myopes seem to have better visual perception than emmetropes.